Association of tumor molecular factors with in‐transit metastasis in primary cutaneous melanoma. (5th March 2022) - Jakub, James W.; Weaver, Amy L.; Meves, Alexander
Abstract: Background: In‐transit metastases (ITM) are a form of locoregional relapse representing intralymphatic metastatic spread and occur in approximately 4–9% of patients with melanoma >1 mm Breslow thickness. Our objective was to evaluate a combination of clinicopathologic risk factors and gene expression biomarkers predictive of ITM risk. Methods: We used PCR to quantify gene expression in diagnostic biopsy tissue across a prospectively designed archival cohort of 854 consecutive thin and intermediate thickness primary cutaneous melanomas. The outcome of interest was ITM >90 days after a melanoma diagnosis. Cox proportional hazard models were fit to estimate each clinicopathologic and molecular characteristic's association with the risk of ITM. Results: The 5‐year cumulative incidence of ITM was 3.2%. Clinical factors univariately associated with an increased risk of ITM were older age, greater Breslow thickness, greater mitotic rate, lower extremity location, ulceration, and a positive SLN biopsy. Of 108 genes tested, five were significantly upregulated and five significantly downregulated when evaluated in Cox models adjusted for age, Breslow thickness, mitotic rate, and lower extremity location. Among the upregulated genes, the strongest association was observed for interleukin‐8 (IL8). Conclusion: A subset of gene expression biomarkers was identified as independently associated with the risk of ITM after adjusting for key covariates. Once sufficiently validated, our results may lead the way to regional therapy trials for a small, selected group of high‐risk patients.